Strategies to increase utilities production panela in Colombia (2014)
This document describes aspects to consider to increase the profits of panela production in Colombia, considering it is the second largest sugarcane producer after India, the issue focuses on the lack of high quality craft production because of the low level of technology in plants and lack of knowledge producers to ensure full use of the raw material, and further understand and comply with Resolution 2546 of 2004 "by the Technical Regulation of emergencies to through which the health requirements that must be met in the production and marketing of sugar cane for human consumption."